2017
DOI: 10.1186/s13059-016-1134-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial degradation of organophosphate insecticides-induces glucose intolerance via gluconeogenesis

Abstract: BackgroundOrganophosphates are the most frequently and largely applied insecticide in the world due to their biodegradable nature. Gut microbes were shown to degrade organophosphates and cause intestinal dysfunction. The diabetogenic nature of organophosphates was recently reported but the underlying molecular mechanism is unclear. We aimed to understand the role of gut microbiota in organophosphate-induced hyperglycemia and to unravel the molecular mechanism behind this process.ResultsHere we demonstrate a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 52 publications
(74 reference statements)
1
55
0
2
Order By: Relevance
“…To date, several reports have shown microbiota structure and microbiome function in the mouse gut under various environmental conditions by metatranscriptomic analysis [22,24,[27][28][29][30][31][32][33][34][35][36][37]. In particular, metatranscriptomic analysis of the mouse gut microbiome during targeted exposure to lard and primary bile acid diet [29], a high-protein diet [31], and vitamin and mineral deficiencies [32] uncovered significant alterations in both bacterial community structure and their gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several reports have shown microbiota structure and microbiome function in the mouse gut under various environmental conditions by metatranscriptomic analysis [22,24,[27][28][29][30][31][32][33][34][35][36][37]. In particular, metatranscriptomic analysis of the mouse gut microbiome during targeted exposure to lard and primary bile acid diet [29], a high-protein diet [31], and vitamin and mineral deficiencies [32] uncovered significant alterations in both bacterial community structure and their gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, metatranscriptomic analysis of the mouse gut microbiome during targeted exposure to lard and primary bile acid diet [29], a high-protein diet [31], and vitamin and mineral deficiencies [32] uncovered significant alterations in both bacterial community structure and their gene expression profiles. In addition to diet conditions, targeted infection Functional dynamics of the mouse gut microbiome revealed by metagenomic and metatranscriptomic analyses with Clostridium difficile [30], specific exposure to organophosphate insecticides [34], and antibiotics [38] alter both the microbiome structure and its functional activity. In contrast, during a host gene deficiency, as in Perilipin-2 (Plin2)-deficient mice, high-fat diet causes the microbiota of Plin2-null mice to undergo significant shifts in transcript expression, despite no distinct change in overall community structure, as compared to wild-type mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Little pieces get eaten by fish, moving up the food chain and seeping into water, often leaching BPA also associated with diabetes risk (Vogel 2009). Another study of 3,080 farmworkers in rural India found that exposure to organophosphate chemicals contributed to diabetes, apparently because the insecticides designed to kill crop pests also interacted with the living microbes crucial to metabolic balance inside people's digestive tracts (Velmurugan et al 2017). This constitutes only one of several mechanisms by which endocrine‐disrupting chemicals can contribute to diabetes, a disease of the endocrine system (see Colborn, Dumanoski, and Myers 1997).…”
Section: Para‐communicable Conditionsmentioning
confidence: 99%
“…Anaerobic culture methods can also be employed to assess the effect of drug or chemical on gut microbiota. 4,9 In this culture method, human or animal faeces can be cultured in presence/ absence of the specific chemical and after the culture period, the changes can be assessed. In our anaerobic culture with faeces and with organophosphate insecticides, we observed the increase in the activity of xenobiotic degrading enzymes, expression of specific genes and degradation of insecticides into glucogenic substrates.…”
Section: Models To Assess Gut Microbiotamentioning
confidence: 99%
“…4-6 food 7-8 and environmental chemicals [9][10][11] and its subsequent effect on physiology and pathology of humans. [4][5][6][7][8][9][10][11] Microbiota is today recognized as an organ of the human body that plays a vital role in human health and disease. 12 Besides their role in body physiology, it plays a key role in digestion and metabolization of xenobiotic compounds.…”
Section: Introductionmentioning
confidence: 99%